PENGEMBANGAN KARAKTER KEBHINEKAAN GLOBAL DALAM MEMBENTUK PROFIL PELAJAR PANCASILA - Solchan Ghozali (Institut Keislaman Abdullah Faqih Gresik, 2020)
This research explains the development of Global Diversity Character in Shaping the Profile of Pancasila Students at SD Al-Muqoddasah Ponorogo. This study used the Descriptive Qualitative Method of phenomenology with primary data sources of Vice Principals, Arabic Language Teachers, and Students of SD Al-Muqoddasah Ponorogo and Secondary data in the form of school document archives. Data Retrieval Techniques through Observation, Interviews, and Documentation, and Data Validity Techniques using source Triangulation Techniques. The results of the research obtained are about the form of Global Kbhinekaan Character Development in Forming a Pancasila Student Profile at Al-Muqoddasah Elementary School carried out in the form of guidance, coaching and introduction to traditions, traditional culture and other people, and fostering mutual respect or tolerance in fellow students in forming students who have the characteristics of a pancasila student profile, such as loving traditions and traditional culture, can respect the traditions and culture of others, can communicate and cooperate well when interacting with other people from any place or circle. The development carried out by the school with the entire teacher council in fostering the global diversity character of students has gone well. Students at SD AL-Muqoddasah have been well developed so that students have the form of pancasila students throughout life. Keyword: Character; Pancasila; Values; Student